Pemanfaatan Media Berbasis Power Point Untuk Menumbuhkan Antusiasme Siswa dalam Materi Pendidikan Agama Islam di Sekolah Dasar - Anis Mahmudah; Andi Prastowo (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
The purpose of this research is to find out the learning of Islamic Religious Education with the use of power point-based media at Surya Menang Elementary School. This research was conducted at Surya Menang State Elementary School, in the odd semester of the 2022/2023 Academic Year. Source of data in this study using primary and secondary sources. Data collection techniques by interviews, while data analysis in this study is data reduction, data presentation, and conclusions. The technique of guaranteeing the validity of the research data is the source triangulation method. The results of the research, namely at Surya Menang State Elementary School, it can be seen that learning using power point-based media can improve the quality of learning in Islamic Religious Education material. Based on the development of learning activities and learning outcomes that were seen during the research, all of them have increased to trigger the enthusiasm and willingness of students to learn and learn Islamic Religious Education materials will also be liked so that they are easily understood and understood by students. This quality improvement can be seen in the process and learning outcomes of Islamic Religious Education materials.